2021
DOI: 10.1002/ajim.23268
|View full text |Cite
|
Sign up to set email alerts
|

Post‐9/11 excess risk of thyroid cancer: Surveillance or exposure?

Abstract: An excess risk of thyroid cancer has been reported in different World Trade Center (WTC)‐dust exposed cohorts. Increased surveillance of these cohorts has been suggested as a potential explanation of this reported excess thyroid cancer risk leading to an increased diagnosis of earlier‐stage thyroid cancers. However, the uncertainty to what extent surveillance or physician bias may be contributing to the reported incidence of thyroid cancer in WTC‐dust exposed populations remains, highlighting the need to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that the high incidence rate of thyroid cancers in children may have an underlying link to height and body mass index (BMI) in the process of growth ( 2 ). Meanwhile, dust and radiation exposure has been reported as a potential risk leading to the increased diagnosis of earlier-stage thyroid cancers ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the high incidence rate of thyroid cancers in children may have an underlying link to height and body mass index (BMI) in the process of growth ( 2 ). Meanwhile, dust and radiation exposure has been reported as a potential risk leading to the increased diagnosis of earlier-stage thyroid cancers ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example of existing conditions, van Gerwen et al (2021) discusses current and future research of thyroid cancer in the WTC population. 50 Some studies have indicated excess thyroid cancer, a disease with few known environmental risk factors, among the exposed population. 15 , 16 , 18 , 20 Some have posited that these results reflect heightened medical surveillance rather than exposure-related disease.…”
Section: Special Issue: Examples Of New Researchmentioning
confidence: 99%
“…Overall cancer rates of WTC Responders were reported to be 6-14% higher than background rates [2,4,[6][7][8][9]. Specifically, excess cases of prostate, thyroid, and skin cancer have been identified among the mostly male Responders [6,[8][9][10], and there is evidence that these cancers may in fact be more aggressive compared with those in the general population [11][12][13]. Additionally, there appears to be a dose-response relationship, whereby WTC Responders with prostate cancer with greater levels of WTC dust exposure present with more advanced stages of disease [11].…”
Section: Introductionmentioning
confidence: 99%